Is It Really Feasible to Use Budesonide–Formoterol as Needed for Mild Persistent Asthma? A Systematic Review and Meta-Analysis - Tong, Xiang; Liu, Tao; Li, Zhenzhen; Liu, Sitong; Fan, Hong (Frontiers in Pharmacology, 2021)
Background: Previous studies suggest that inhaled budesonide-formoterol used as needed could effectively reduce the severe exacerbation of mild persistent asthma. However, there are some differences between these studies, so we conducted a meta-analysis. Methods: We searched PubMed, Ovid MEDLINE, Cochrane Library and several web search engines to screen the literature until March 25, 2020 and used risk ratios (RR), odds ratios, hazard ratios (HR) and weighted mean differences with 95% confidence intervals (CI) to evaluate the pooled effects. Adult patients with mild persistent asthma who used budesonide–formoterol as needed were included in this study. The primary outcome was to investigate the superiority of budesonide–formoterol as needed in reducing severe exacerbations in patients with mild persistent asthma. STATA 12.0 software was used for statistical analysis. Results: Across all 4 articles, 4023 patients used budesonide–formoterol as needed (budesonide–formoterol group), 4042 patients used budesonide maintenance plus short-acting β2-agonist (SABA) as needed (budesonide group), and 1500 patients used SABA as needed (SABA group). The results showed that the incidence of severe exacerbations and the time to first severe exacerbation in the budesonide–formoterol group were significantly different from those for the SABA group (RR=0.46, 95% CI=0.36-0.59, P<0.001; HR=0.43, 95% CI=0.33-0.56, P<0.001; respectively), but there was no difference between the budesonide–formoterol group and budesonide group (RR=0.86, 95% CI=0.62-1.04, P=0.093; HR=0.77, 95% CI=0.57-1.03, P=0.079; respectively). There were statistically significant differences in the forced expiratory volume in 1 second and in the responses to the Asthma Control Questionnaire-5 between the budesonide-formoterol group and the SABA group, but the differences were not clinically significant. In addition, the daily dose of budesonide in the budesonide–formoterol group was significantly lower than that in the budesonide group, and there was no difference in the incidence of adverse events among the three groups. Conclusion: In summary, budesonide–formoterol used as needed may reduce severe exacerbation in adolescent/adult patients with mild persistent asthma.